2009
DOI: 10.4315/0362-028x-72.10.2088
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella in Processed Chicken Products during Frozen Storage

Abstract: Frozen chicken products have been identified recently as a cause of salmonellosis. At least eight salmonellosis outbreaks from 1998 to 2008 have implicated undercooked frozen chicken nuggets, strips, and entrees as infection vehicles. Thus, the presence of Salmonella in frozen products may pose an infection risk if the product is improperly cooked. The objective of this study was to assess the survivability of Salmonella during frozen storage (-20 degrees ) when inoculated in processed chicken products. Four S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Even though the major production load of the meat plant was focused on ground meat, Salmonella was found in markedly lower percentage (P b 0.05) in these products, than in poultry. The high occurrence of the pathogen in poultry raw materials and final products (27.1%) was slightly lower compared with the 39.5% of chicken carcasses in Greece (Zdragas et al, 2012), the 34% in Turkey (Yildirim et al, 2011) or the 35.8% in Spain (Dominguez and Schaffner, 2009). However, despite the lower occurrence here compared to other studies, our findings still show markedly higher occurrence of Salmonella than the 4.1% reported at the EU level in 2012 for fresh broiler meat at processing and retail, as well as the 9.7% prevalence reported for Greece in the same year (EFSA ECDC, 2014).…”
Section: Occurrence and Serotyping Of Salmonella Sppmentioning
confidence: 81%
“…Even though the major production load of the meat plant was focused on ground meat, Salmonella was found in markedly lower percentage (P b 0.05) in these products, than in poultry. The high occurrence of the pathogen in poultry raw materials and final products (27.1%) was slightly lower compared with the 39.5% of chicken carcasses in Greece (Zdragas et al, 2012), the 34% in Turkey (Yildirim et al, 2011) or the 35.8% in Spain (Dominguez and Schaffner, 2009). However, despite the lower occurrence here compared to other studies, our findings still show markedly higher occurrence of Salmonella than the 4.1% reported at the EU level in 2012 for fresh broiler meat at processing and retail, as well as the 9.7% prevalence reported for Greece in the same year (EFSA ECDC, 2014).…”
Section: Occurrence and Serotyping Of Salmonella Sppmentioning
confidence: 81%
“…during transportation from a retail outlet to a consumer's home). Salmonella numbers are reduced under frozen storage conditions but salmonellosis outbreaks from 1998 to 2008 due to consumption of frozen products showed that bacteria can survive freezing and Salmonella may pose an infection risk if the product is improperly cooked [57]. Thus, freezing cannot be considered as an adequate control step.…”
Section: Primary and Secondary Poultry Processing And Retailmentioning
confidence: 99%
“…In this study, we used a quickfreezing process, and little reduction of the bacteria was observed after freezing/storage. Dominguez and Schaffner (2009) reported the survival of Salmonella on chicken products after 3 months of frozen storage at −20 o C, which concurred with the results of this study for the non-dipped fillet controls also stored for 3 months at −20 o C. However, there was a significant (p < 0.05) reduction (2 log CFU/g) in Salmonella counts for the 1.5% TSP wash and frozen samples recovered after 3-months storage, but no further reduction occurred during the remainder of the frozen study. Gram-negative bacteria after a sublethal injury (TSP dip) are more prone to the lethal effects of freezing (Venugopal, 2005), which would explain the significant Salmonella reduction in the TSP dipped samples compared to the Gram-positive LM sample.…”
Section: The Dip and Freezing Studymentioning
confidence: 99%